2016
DOI: 10.1002/pam.21954
|View full text |Cite
|
Sign up to set email alerts
|

Testing the School‐to‐Prison Pipeline

Abstract: The School-to-Prison

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 29 publications
5
101
0
Order By: Relevance
“…Our review of prior research indicated that the more rigorous prior studies (Na & Gottfredson, 2013;Owens, 2016;Swartz et al, 2016;Weisburst, 2019) found that SRO presence or receipt of CIS grants were related to increased recording of drug crimes, crimes involving weapons, and serious violent crimes as well as increased severity in school responses to student crime and disorder. With one exception, our findings mirror these: Although the direction of effects on serious violent offenses was consistent with prior research, we found no statistically significant effects on these offenses.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our review of prior research indicated that the more rigorous prior studies (Na & Gottfredson, 2013;Owens, 2016;Swartz et al, 2016;Weisburst, 2019) found that SRO presence or receipt of CIS grants were related to increased recording of drug crimes, crimes involving weapons, and serious violent crimes as well as increased severity in school responses to student crime and disorder. With one exception, our findings mirror these: Although the direction of effects on serious violent offenses was consistent with prior research, we found no statistically significant effects on these offenses.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…More longitudinal studies are needed. The most rigorous studies (Owens, 2016 andWeisburst, 2019) related receipt of CIS grants to increases in school crime outcomes, but could not connect the receipt of grants directly to the hiring of SROs in the schools included in the study. The current study complements these rigorous studies by relating month-to-month variation in school-level disciplinary outcomes to the timing of the placement of CIS grant-related SROs in those same schools.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Owens () is a notable exception; it examines the impact of changes in police hiring on arrests in and out of school for students of different ages using national data at the police department and county level. Similar to the current study, Owens () estimates her model using quasi‐experimental variation in federal Community Oriented Police Services (COPS) grant funding for school police. She finds that expansions in school police increase property and violent arrests for children younger than high school age on school grounds and increase drug arrests for high school‐aged juveniles off of school grounds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In short, these studies have provided mixed findings. Some studies report positive effects of SROs, though, with one notable exception (Owens ), these are mostly based on school administrators' (e.g., May et al ; Time and Payne ) or students' (e.g., Jackson ) perceptions of school safety rather than more objectively measured outcomes. A greater number of studies finds null or mixed impacts of SROs (Devlin and Gottfredson ; Zhang ), or negative results, including that the presence of SROs is associated with increased exclusionary discipline (Fisher and Hennessy ), higher rates of arrest of students for minor behaviors (Na and Gottfredson ; Theriot ), or that it reshapes the school social climate in ways that can be harmful to youth (Kupchik ).…”
Section: Background On Policing In Schoolsmentioning
confidence: 99%